Antioxidative and osmoprotecting mechanisms in carrot plants tolerant to soil salinity - Iwona Kamińska; Aneta Lukasiewicz; Magdalena Klimek-Chodacka; Olga Długosz-Grochowska; Julia Rutkowska; Kamil Szymonik; Rafal Baranski (Scientific Reports, 2022)
Abstract Soil salinization is a growing problem for agriculture worldwide and carrot is one the most salt-sensitive vegetable species. However, some varieties are capable of withstanding high salt concentrations due to unknown genetic and physiological mechanisms. The aim of this work was to reveal protecting mechanisms against osmotic and ionic stresses that contribute to salt tolerance in carrot. For this purpose, changes in biochemical traits due to soil salinity occurring in the salt-tolerant and salt-sensitive plants were determined. The obtained results showed that the tolerance of the salt-tolerant variety was partially determined constitutively, however, the exposition to saline soil triggered a physiological response that was more evident in the root than in the leaves. The most noticeable changes were the high increase in the content of osmoprotective proline and other low molecular antioxidants such as glutathione and ascorbic acid, and the decrease in the ratio of reduced to oxidized glutathione forms. These changes imply an efficient operation of the ascorbate–glutathione cycle that together with a high activity of antioxidative enzymes such as peroxidases, indicate on the induction of mechanisms associated mainly with protection against excessive reactive oxygen species.